1984
DOI: 10.1063/1.447422
|View full text |Cite
|
Sign up to set email alerts
|

Observation of high vibrational excitation in HCN molecules produced from 193 nm photolysis of 1,3,5-triazine

Abstract: Infrared emission from the ν2 bending mode and ν3 C–H stretching mode of HCN have been observed following 193 nm pulsed excimer laser photolysis of 1,3,5-triazine. Using a simple harmonic oscillator analysis, the number of ν2 bending quanta produced in HCN from photolysis of sym-triazine was found to be 70 times larger than the number of ν3 C–H stretching quanta. The combination of a high density of bending vibrational states in HCN and favorable geometry changes which occur in going from 1,3,5-triazine to thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 18 publications
1
40
0
Order By: Relevance
“…This last mechanism is supported by the computational studies of Politzer and coworkers [8] as well as the classical dynamics calculations of Sewell and Thompson [9]. There is experimental and theoretical evidence that the aromatics 1,3,5-triazine (s-triazine) [10][11][12][13][14][15][16] and s-tetrazine [17][18][19][20] also undergo three-body unimolecular decomposition when they are highly vibrationally excited on the ground electronic surface, as they are in a thermal reaction. However, the dissociation of the infamous substituted triazine, melamine, 2,4,6-triamino-1,3,5-triazine, evidently follows a radical path [21].…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…This last mechanism is supported by the computational studies of Politzer and coworkers [8] as well as the classical dynamics calculations of Sewell and Thompson [9]. There is experimental and theoretical evidence that the aromatics 1,3,5-triazine (s-triazine) [10][11][12][13][14][15][16] and s-tetrazine [17][18][19][20] also undergo three-body unimolecular decomposition when they are highly vibrationally excited on the ground electronic surface, as they are in a thermal reaction. However, the dissociation of the infamous substituted triazine, melamine, 2,4,6-triamino-1,3,5-triazine, evidently follows a radical path [21].…”
Section: Introductionmentioning
confidence: 84%
“…9, but our recent study of HCN itself [48] showed no indication of isomerization, so this seems quite unlikely. Perhaps the HCN is somehow formed with close to equilibrium HNC [11].…”
Section: Dissociationmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, the molecular structure of 1,3,5-triazine ( 12 r(CÀH) 108.9(2) pm, and <(CNC) 113.82 (9) [415]. The photodissociation of symtriazine has been widely studied [416][417][418][419][420][421][422][423][424]. A computational study of the stability, homodesmotic stabilization energy, electron distribution and magnetic ring current of 1,3,5-triazines has been described [53].…”
Section: 41mentioning
confidence: 99%
“…[43][44][45][46][47][48][49] Sym-triazine is just one of a handful of molecular species known to undergo multibody dissociation. [43][44][45][46][47][48][49] Sym-triazine is just one of a handful of molecular species known to undergo multibody dissociation.…”
Section: B Photodissociation Of Sym-triazine and The Coherent Transimentioning
confidence: 99%